organizational culture, job training, work discipline, employee performance - Hafizh Adrian Imani; Arie Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The inventory system at the Panglima coffee shop is done manually. So this research aims to build an inventory system at the Panglima Kopi shop based on web, to cover the process of recording goods, incoming goods, outgoing goods and controlling data transaction reports. As well as stock stock using the prototyping system development method that includes system analysis using cross-functional diagrams. Modeling in this system uses the Unified Modeling Language (UML), this development system is built with PHP programming language and MySQL database and by using Black Box type Alpha testing. The purpose of building this system is to make it easier to use it in recording inventory at Panglima Kopi shops, and to print transaction and goods reports.